The determination modulli of iron, aluminum and magnesium materials using ultrasonic testing / Ahmad Shafiq Zainuddin - Zainuddin, Ahmad Shafiq (Faculty Of Applied Sciences, 2017)
The three sample of different type of materials (iron, aluminum and magnesium) are used to determine the moduli properties. They were undergoing ultrasonic testing method to determine the longitudinal and shear wave velocity. In determining of wave velocity, we use Echograph instrument to measure time of wave travel through the sample in longitudinal and transverse. From this velocity of wave, the value of moduli (MOE, shear modulus and poisson rato) can be calculated by using a specific formula. From this experiment, it can be conclude that the iron have the highest value among the samples in MOE and shear modulus but not in poisson ratio. The aluminum sample was the highest in poisson ratio. The magnesium was low on three types of moduli value because it is popular as a brittle material.